Pengaruh pemahaman perpajakan, insentif pajak, dan sanksi perpajakan terhadap kepatuhan wajib pajak orang pribadi pemilik UMKM di Kota Manado - The, Gabriela Stefanny; Lambey, Robert; Datu, Christian (Riset Akuntansi dan Portofolio Investasi, 2024)
Taxation is a crucial aspect that can overcome economic difficulties and contribute to the sustainable development of the country. The purpose of this research is to determine the effect of tax understanding, tax incentives and tax sanctions on tax compliance among individual taxpayers who own MSMEs in Manado, partially and simultaneously. The sample data consists of 100 individual taxpayers who own MSMEs in Manado. This study adopts an associative quantitative research approach using multiple linear regression analysis. The results indicate that partially, tax understanding and tax incentives have a positive and significant effect on compliance among individual taxpayers who own MSMEs in Manado City, and tax sanctions have no significant effect on compliance among these taxpayers. In addition, tax understanding, tax incentives and tax sanctions have a simultaneous effect on compliance among individual taxpayers who own MSMEs in Manado City.